2016
DOI: 10.1016/j.tet.2015.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting AI-2-mediated quorum sensing through C5-analogue synthesis and biochemical analysis

Abstract: Autoinducer-2 (AI-2)-mediated quorum sensing (QS) is utilised for both intra- and inter-species communication by a wide variety of bacteria. An understanding of the mechanism of this communication has the potential to elucidate new targets for antibacterial therapeutics. Herein, we report the synthesis of DPD analogues with modified dynamic equilibria and the evaluation of their behaviour in Gram-negative bacteria. None of the compounds showed modulation of QS in S. Typhimurium, and although no antagonism of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
(30 reference statements)
1
20
0
3
Order By: Relevance
“…They play acrucial role in the regulation of an umber of key virulence factors,s uch as adhesins,h emolysins,a nd staphylocoagulase. [207][208][209] Although possible sites for modification are limited, variations at C1 and C4 led to the discovery of C1propyl-and butyl-DPDs as potent AI-2 QS antagonists in S. typhimurium and native DPD and C4-ethoxyl-and proxyl-DPDs as AI-2-based QS agonists in V. harveyi AI-2 (Figure 15 c). [198] Muir and co-workers developed AIP-II analogues as AgrA inhibitors [199][200][201] and Blackwell and co-workers recently published as eries of studies on AIP mimetics with af ocus on AIP-III.…”
Section: Quorum Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…They play acrucial role in the regulation of an umber of key virulence factors,s uch as adhesins,h emolysins,a nd staphylocoagulase. [207][208][209] Although possible sites for modification are limited, variations at C1 and C4 led to the discovery of C1propyl-and butyl-DPDs as potent AI-2 QS antagonists in S. typhimurium and native DPD and C4-ethoxyl-and proxyl-DPDs as AI-2-based QS agonists in V. harveyi AI-2 (Figure 15 c). [198] Muir and co-workers developed AIP-II analogues as AgrA inhibitors [199][200][201] and Blackwell and co-workers recently published as eries of studies on AIP mimetics with af ocus on AIP-III.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…[95,205] In view of the role of AI-2 for interspecies communication, [206] various modifications on the AI-2 precursor 4,5dihydroxy-2,3-pentanedione (DPD) have been carefully examined. [207][208][209] Although possible sites for modification are limited, variations at C1 and C4 led to the discovery of C1propyl-and butyl-DPDs as potent AI-2 QS antagonists in S. typhimurium and native DPD and C4-ethoxyl-and proxyl-DPDs as AI-2-based QS agonists in V. harveyi AI-2 (Figure 15 c). [210,211] Further manipulation of this pathway was observed with fimbrolide natural products,w hich cause phenotypic changes in various bacterial strains.C hemical proteomics confirmed that fimbrolides inhibit AI-2 signaling by targeting LuxS.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[197,200] Beispielsweise konnte gezeigt werden, dass Savirin und w-Hydroxyemodin die Signalübertragung in S. aureus verhindern, indem sie an den Response-Regulator AgrA binden, was in einem Mausmodell zu einer vollständigen Entfernung der Bakterienlast führte. [207][208][209] Auch wenn die Anzahl an mçglichen Modifikation begrenzt ist, führten Veränderungen an C1 und C4 zur Entdeckung von C1-Propyl-und Butyl-DPD als neue AI-2basierte QS-Antagonisten in S. typhimurium und DPD selbst sowie C4-Ethoxyl-und Proxyl-DPDs als AI-2-basierten QS-Agonisten in V. herveyi (Abbildung 15 c). [207][208][209] Auch wenn die Anzahl an mçglichen Modifikation begrenzt ist, führten Veränderungen an C1 und C4 zur Entdeckung von C1-Propyl-und Butyl-DPD als neue AI-2basierte QS-Antagonisten in S. typhimurium und DPD selbst sowie C4-Ethoxyl-und Proxyl-DPDs als AI-2-basierten QS-Agonisten in V. herveyi (Abbildung 15 c).…”
Section: Angewandte Chemieunclassified
“…[95,205] Im Hinblick auf die Rolle von AI-2 bei der artübergreifenden Kommunikation [206] wurden vielfältige Modifikation am AI-2-Vorläufer 4,5-Dihydroxy-2,3-pentandion (DPD) erforscht. [207][208][209] Auch wenn die Anzahl an mçglichen Modifikation begrenzt ist, führten Veränderungen an C1 und C4 zur Entdeckung von C1-Propyl-und Butyl-DPD als neue AI-2basierte QS-Antagonisten in S. typhimurium und DPD selbst sowie C4-Ethoxyl-und Proxyl-DPDs als AI-2-basierten QS-Agonisten in V. herveyi (Abbildung 15 c). [210,211] Weitere Mçglichkeiten zur Manipulation dieses Stoffwechselweges ergaben sich durch die Fimbrolid-Naturstoffe,w elche phänotypische Veränderungen in verschiedenen Bakterienstämmen zur Folge hatten.…”
Section: Angewandte Chemieunclassified